2018
DOI: 10.18357/ijcyfs92201818216
|View full text |Cite
|
Sign up to set email alerts
|

Facing the Generation Chasm: The Parenting and Teaching of Generations Y and Z

Abstract: Abstract:The Millennials, or Generation Y, have been receiving increasing attention as these young people have entered tertiary institutions and the workplace over the past decade. Their behavior towards authority is coming under sharper scrutiny as they prepare to move into leadership positions. For example, their assertiveness received both positive and negative attention in the South African media during the "fees must fall" campaign. While parents, caregivers, teachers, and employers wonder about the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 8 publications
2
26
0
10
Order By: Relevance
“…According to a study, reviewing the education given to the generations and making use of learning and teaching strategies that can be used to understand and guide the Y and Z generations can help prevent generation gap that will threaten healthy relationships among young people. 17 In another study, Barnes, Marateo, and Ferris 18 found that combining technology with learning, reducing lecture times, shaping homework to increase the participation, and using electronic tools does not necessarily translate to an increase in literacy or critical thinking skills. Generation Z requires innovative teaching using different forms of technology.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study, reviewing the education given to the generations and making use of learning and teaching strategies that can be used to understand and guide the Y and Z generations can help prevent generation gap that will threaten healthy relationships among young people. 17 In another study, Barnes, Marateo, and Ferris 18 found that combining technology with learning, reducing lecture times, shaping homework to increase the participation, and using electronic tools does not necessarily translate to an increase in literacy or critical thinking skills. Generation Z requires innovative teaching using different forms of technology.…”
Section: Discussionmentioning
confidence: 99%
“…At one level, many of the generation often identified as Generation Z (students born in the 1990's) have lived in a world awash with digital, networked technologies. At another level, however, members of this generation may not fully understand how to maximize the affordances of current digital technologies and apply them to either their own learning or to designing learning experiences (Mosca et al, 2019;Swanzen, 2018).…”
Section: Developing Future-ready Educatorsmentioning
confidence: 99%
“…Karakterisik generasi Z adalah fasih dengan teknologi dan menghabiskan rata-rata 9 jam per hari bersama ponsel mereka (Daugherty & Hoffman, 2014), pragmatis, waspada, mengutamakan kebersamaan, berkomunikasi dengan gambar, realistis, dan kesadaran kolektif. Mereka menginginkan perhatian terhadap kebutuhan informasi yang berbeda untuk setiap individu, kesempatan memberikan umpanbalik secara langsung atas apa yang diterima, teknik kolaborasi aktif pihak-pihak yang terlibat, cara yang modern dan menyenangkan, dan mengonsumsi informasi yang mudah diakses dan dipahami (Swanzen, 2018).…”
Section: Pendahuluanunclassified